Contra‐Thermodynamic, Photocatalytic E→Z Isomerization of Styrenyl Boron Species: Vectors to Facilitate Exploration of Two‐Dimensional Chemical Space. Issue 12 (21st February 2018) - Molloy, John J.; Metternich, Jan B.; Daniliuc, Constantin G.; Watson, Allan J. B.; Gilmour, Ryan
Abstract: Designing strategies to access stereodefined olefinic organoboron species is an important synthetic challenge. Despite significant advances, there is a striking paucity of routes to Z ‐α‐substituted styrenyl organoborons. Herein, this strategic imbalance is redressed by exploiting the polarity of the C(sp 2 )−B bond to activate the neighboring π system, thus enabling a mild, traceless photocatalytic isomerization of readily accessible E ‐α‐substituted styrenyl BPins to generate the corresponding Z ‐isomers with high fidelity. Preliminary validation of this contra‐thermodynamic E → Z isomerization is demonstrated in a series of stereoretentive transformations to generate Z ‐configured trisubstituted alkenes, as well as in a concise synthesis of the anti‐tumor agent Combretastatin A4. Abstract : It's EZ : Exploitation of the polarity of the C(sp 2 )−B bond to activate the neighboring π system enables a mild, traceless photocatalytic isomerization of readily accessible E ‐α‐substituted styrenyl BPins to generate the corresponding Z ‐isomers with high fidelity. The method is used for a series of stereoretentive transformations to generate Z ‐configured trisubstituted alkenes, as well as in a concise synthesis of the anti‐tumor agent combretastatin A4.